ANALISIS CERPEN “BADAI YANG REDA” KARYA FAUZIA A: PERSPEKTIF SOSIAL DAN PSIKOLOGIS DALAM PENCARIAN JATI DIRI - Listanto, Firgiawan; Arfiah, Siti; Yunus, Syarifudin (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study uses a qualitative-descriptive method with a literary approach, especially a sociological and psychological approach to literature. This method was chosen because it is appropriate for revealing the meaning contained in literary texts in depth, especially those related to social dynamics and the psychological conditions of the characters in the short story. This approach also allows researchers to analyze how social structures and environmental pressures influence the main character's inner journey in finding their identity. The short story "Badai yang Reda" by Fauzia A describes the main character's inner journey in finding their identity amidst social pressure and psychological conflict. From a social perspective, this story highlights the role of the environment, family, and expectations of coastal communities that shape the character's identity. The main character experiences a dilemma between her desire for freedom and her attachment to tradition and social obligations. This tension shows how social structures not only create roles, but also become a source of pressure that limits the individual's space to explore and express themselves.